May the flexural strength of ceramics be influenced by salivary pH? - Caroline Cotes; Vanessa Cruz Macedo; Mariana Camillo; Bruna Lara; Rodrigo Carvalho; Carolina Martinelli; Estevao Kimpara (Brazilian Dental Science)
Objective. This study purpose was compare the three-point flexural strengths of 50 feldspathic ceramic after storage in artificial saliva. Material and methods. The bars were luted with resin cement and subjected to storage in artificial saliva of different pHs. Results.  The values of flexural strength were significantly higher for the bars stored in distilled water, at neutral and basic pH, when compared with the results for the bars stored in acidic pH and in acid/basic pH. Conclusions. Storage for 30 days in artificial saliva at acidic pH, or alternating between acidic and basic pH, can reduce the mechanical properties of ceramics.